Embedding Writing Support Within a Psychology Academic Skills Module: A Case Study - James, Alana I. (Journal of Academic Writing, 2018)
A Psychology academic skills module and challenges in its delivery are outlined. Adaptations described include embedding specialist support for the teaching of academic writing and linking content to assessments and careers. Increased student satisfaction and qualitative feedback indicated that changes were beneficial. The need for further evaluation is discussed.